Seroprevalence and Associated Outcomes of Parvovirus B19 Infection in Human Immunodeficiency Virus Patients: A Systematic Review - Mohamed, Sagad O. O.; Mohamedelmugadam, Reem A. A.; Almardi, Safa A. M.; Ahmed, Tassnem H. M.; Ibrahim, Malaz E. H.; Mohamedali, Abdalla O. O. (Avicenna Journal of Medicine, 2024)
Several case reports have highlighted the presence of serious clinical outcomes in patients with human immunodeficiency virus (HIV) related to parvovirus B19 (PVB19). However, epidemiological studies have produced inconsistent and varying results regarding the prevalence of PVB19 and its associated clinical outcomes in this population. These inconsistencies highlight the need for a thorough summary and analysis of present data to better understand burden and impact of PVB19 on HIV patients. This review aims to provide an overview of current evidence and identify areas for further research.Following the Meta-analyses of Observational Studies in Epidemiology (MOOSE) guidelines, a comprehensive search was conducted across Medline/PubMed, Google Scholar, and World Health Organization Virtual Health Library Regional Portal. The pooled prevalence with the corresponding 95% confidence interval (CI) was measured using Comprehensive Meta-Analysis Software version 3.3. Publication bias was estimated based on Begg's test, Egger's test, and examination of the funnel plots.A total of 16 studies, with 2,122 HIV patients, were included in the meta-analysis. The pooled prevalence of detecting anti-PVB19 immunoglobulin G, anti-PVB19 immunoglobulin M, and PVB19 DNA particles among HIV patients was 43.6% (95% CI: 23.5–66.1%), 5.10% (95% CI: 2.10–12.10%), and 6.40% (95% CI: 4.10–9.90%), respectively. In the overall population of HIV patients, most of the included studies did not establish a statistically significant association between PVB19 infection and the occurrence of anemia.PVB19 infection is commonly detected in individuals with HIV. However, anemia due to PVB19 is not common in this population. Findings from a few studies suggest that PVB19 infection may contribute to anemia in individuals with advanced HIV disease or significant immunosuppression. Additional research is needed to confirm and clarify these relationships in individuals with HIV, particularly those with compromised immune systems.
Keywords: human immunodeficiency virus; HIV; anemia; parvovirus B19; PVB19